Hydrothermal crystallization and modification of surface hydroxyl groups of anodized TiO2 nanotube-arrays for more efficient photoenergy conversion - Kuo, Yu-Yen; Li, Tze-Huei; Yao, Jing-Neng; Lin, Chiung-Yuan; Chien, Chao-Hsin (Electrochimica acta, 2012)
[Display omitted] ► Hydrothermally crystallized nanotubes show improved cyrstallinity. ► Basic hydrothermal pH induces morphological transformation of the nanotubes. ► Acidic hydrothermal pH induces transition of surface hydroxyl groups. ► Adsorption of bipyridyl dye on nanotubes is greatly influenced by hydrothermal pH. ► The efficiency of nanotube solar cell increased from 6.40% to 7.13%. This paper describes a crystallization method for anodized TiO2 nanotube-array using a hydrothermal process. Pre-sintered TiO2 nanotube-array could further crystallize without experiencing a collapse of the nanotubes under the hydrothermal environment. Applying the hydrothermal crystallization method, the transition of surface bonds of nanotube from Ti–O to Ti–OH/Ti–OH2 can be controlled by acidic hydrothermal pH levels. Dissolution and structural transformation of nanotubes was easily induced if the hydrothermal environment became basic. These effects depicted great influence on the anchoring of carboxylate groups on the surface of TiO2 nanotubes and affected the performance of the dye-sensitized solar cell utilizing the hydrothermally crystallized TiO2 nanotubes as the photoelectrode. The photoenergy conversion efficiency increased from 6.40% for thermally annealed nanotubes to 7.13% for hydrothermally crystallized ones under illumination of 100mWcm−2.